Grandparents Raising Grandchildren: Understanding Relationships - Part 1 - Millie Ferrer; Angela Falcone; Joe Pergola (EDIS, 2002)
This document is FCS 2190-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2002. Its goal is to provide grandparents with information to better understand family relationships.